From homemakers to breadwinners? How mandatory kindergarten affects maternal labour market attachment - Selina Gangl; Martin Huber (ZBW - Leibniz Information Centre for Economics, 2021)
We analyse the effect of a mandatory kindergarten for four-year-old children on maternal labour supply in Switzerland by using two quasi-experiments: Firstly, we use a large administrative dataset and apply a non-parametric Regression Discontinuity Design to evaluate the effect of the reform at the birthday cut-off for entering the kindergarten in the same versus in the following year. Secondly, we complement this analysis by exploiting spatial variation and staggered treatment implementation of the reform across cantons (administrative units in Switzerland) in a Difference-in-Differences approach using a Swiss household survey. All in all, the results suggest that if anything, mandatory kindergarten increases the labour force attachment of mothers very moderately. The effects are driven by mothers earning less than the median annual work income of 15,706 CHF and by older mothers (>37).
Keywords: H40; J13; J18; J21; J22; 330; mandatory kindergarten; maternal labour supply; regression discontinuity design; difference-in-differences; variable selection